Things That Become Visible, for a While, Can Leave a Residue; Comment on "Ensuring Global Health Equity in a Post-pandemic Economy" - Nele Jensen (Kerman University of Medical Sciences, 2023)
Professor Labonté's editorial is an important intervention that reiterates the stark socio-economic and health inequities that were exposed and perpetuated during the coronavirus disease 2019 (COVID-19) pandemic to call on the public health community to hold politicians to account for their promises of 'building back better.' The editorial makes present how quickly pandemic promises seem to have become dislodged by an ostensibly endless cycle of political and economic crises. But it also expresses a hope that lessons from the pandemic will eventually serve to challenge prevailing (economic) policy orthodoxy and feed a collective demand for more progressive social, economic and environmental justice-oriented politics.